In Vitro Assessment of Magnetic Liposomal Paclitaxel Nanoparticles as a Potential Carrier for the Treatment of Ovarian Cancer - Sara Yousefi Aldashi; Zahra Saffari; Hasan Ebrahimi Shahmabadi; Azim Akbarzadeh (Tabriz University of Medical Sciences, 2021)
Purpose: This study aimed to evaluate the role of magnetic liposome nanoparticles (ML NPs) as a carrier for paclitaxel (PTX) for the treatment of ovarian cancer in vitro. Methods: Magnetic NPs (MNPs) were synthesized by chemical co-precipitation method. The resulting NPs were characterized in terms of size, size distribution, zeta potential, drug encapsulation efficiency (EE), drug release pattern, and cytotoxicity effects. Results: The size and zeta potential of PTX-PEG-L and PTX-PEG-ML NPs were determined to be 296, 198 nm; -20, and -19 mV, respectively. Also, their drug encapsulation efficiencies were determined to be 97% and 96%, respectively. It was found that PTX-PEG-ML NPs, compared to PTX-PEG-L NPs, caused a reduction (11%) in the rate of drug release. The cytotoxicity of the drug-loaded NPs was assessed using 3-[4,5-dimethylthiazole-2-yl]-2,5-diphenyltetrazolium bromide (MTT) assay against human ovarian epithelial cancer (A2780CP) cells, and the results demonstrated that PTX-PEG-ML NPs caused higher cytotoxicity (by 14%) compared to PTX-PEG-L NPs (IC50: 1.88 ± 0.09 and 2.142 ± 0.1 µM, respectively). Conclusion: Overall, the results of this study suggest that PTX-PEG-ML NPs could be considered as a therapeutic candidate for the treatment of ovarian cancer.